2022
DOI: 10.1186/s12902-022-01031-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cotadutide drug on patients with type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: Background The food and drug administration approved many drugs to treat diabetes mellitus, but those drugs do not have a noticeable effect on weight management. Recently, glucagon-like peptide 1 agonist known as Cotadutide serve as a potent drug in treating type 2 diabetes by reducing blood glucose levels and body weight indices. This study aimed to explore the safety and efficacy of Cotadutide as a treatment for type 2 diabetes individuals. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Although glucagon and GLP-1 have distinct effects on glucose levels, their effects on food intake may be additive [ 88 ], leading to more significant body-weight reduction. Several OXM derivatives are under clinical trials, for example, cotadutide, a once-daily GCGR/GLP-1R dual agonist, has shown promising impacts on glycemic control, body weight, and liver fat reduction [ 89 ].…”
Section: Functional Molecules Targeting Glp-1rmentioning
confidence: 99%
“…Although glucagon and GLP-1 have distinct effects on glucose levels, their effects on food intake may be additive [ 88 ], leading to more significant body-weight reduction. Several OXM derivatives are under clinical trials, for example, cotadutide, a once-daily GCGR/GLP-1R dual agonist, has shown promising impacts on glycemic control, body weight, and liver fat reduction [ 89 ].…”
Section: Functional Molecules Targeting Glp-1rmentioning
confidence: 99%
“…In a Bayesian network meta-analysis study, the effective role of Chinese tradition medicine against T2DM was deliberated comparing with western medicines [ 152 ]. The cotadutide drug has been a potent drug in treating T2DM which has been effective in decreasing glucose levels, haemoglobin A, and body weight [ 156 ]. The Chinese medicine Astragali Radix-Coptis Rhizoma and Allium sativum L. was used to treat T2DM were its mechanistic action using network pharmacology was explained in a study [ 171 , 172 ].…”
Section: Traditional Indian Medicinal Plants To Treat T2dm and Pdmentioning
confidence: 99%
“…Another dual agonist consisting of GLP‐1 and glucagon (GCG) receptor agonist, named cotadutide, yet not approved by the FDA, has been shown to reverse hepatic steatosis in murine models and there are currently various ongoing trials to evaluate its efficacy on the metabolic consequences of diabetes 82 . The weight‐lowering effects of cotadutide appear to be less impressive than those of tirzepatide and some GLP‐1 RA 80 , endorsing the hypothesis that effects on NAFLD are not exclusively related to weight loss.…”
Section: Dual and Triple Agonistsmentioning
confidence: 99%